2019
DOI: 10.1093/mnras/stz1971
|View full text |Cite
|
Sign up to set email alerts
|

A multiwavelength study of the debris disc around 49 Cet

Abstract: In a multiwavelength study of thermal emission and scattered light images we analyse the dust properties and structure of the debris disc around the A1-type main-sequence star 49 Cet. As a basis for this study, we present new scattered light images of the debris disc known to possess a high amount of both dust and gas. The outer region of the disc is revealed in former coronagraphic H-band and our new Y-band images from the Very Large Telescope SPHERE instrument. We use the knowledge of the disc’s radial exten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 94 publications
5
12
0
Order By: Relevance
“…A similar explanation applies to 49Cet, HD377, and V419Hya, highlighting the sensitivity differences between ground-based polarimetry and space-based total intensity observations. In the case of 49Cet, we also did not reach the contrast needed to detect the ring in total intensity at r<1 4, similar to the SPHERE results that did not detect the disk inward of 1 4 with approximately the same integration time in the H band (Choquet et al 2017) or more than double our greatest integration time and field rotation in the Y band (Pawellek et al 2019).…”
Section: Nondetectionssupporting
confidence: 85%
See 1 more Smart Citation
“…A similar explanation applies to 49Cet, HD377, and V419Hya, highlighting the sensitivity differences between ground-based polarimetry and space-based total intensity observations. In the case of 49Cet, we also did not reach the contrast needed to detect the ring in total intensity at r<1 4, similar to the SPHERE results that did not detect the disk inward of 1 4 with approximately the same integration time in the H band (Choquet et al 2017) or more than double our greatest integration time and field rotation in the Y band (Pawellek et al 2019).…”
Section: Nondetectionssupporting
confidence: 85%
“…Related to the effects of contrast, we can attribute nondetections of some HST-resolved disks to their intrinsically low scattered-light surface brightnesses. These include 49Cet (Choquet et al 2017;Pawellek et al 2019), HD377, TWA25 (Choquet et al 2016), and V419Hya (HD 92945; Golimowski et al 2011;Schneider et al 2014). For example, the TWA25 disk has a peak surface brightness of ∼40 μJy arcsec −2 at r=1″and an overall mean of 28±5 μJy arcsec −2 , based on the model of NICMOS 1.6 μm (F160W) observations presented by Choquet et al (2016).…”
Section: Nondetectionsmentioning
confidence: 99%
“…Other debris disks that were considered but not included in the sample are the disks around 𝛽 Pictoris (Millar-Blanchaer et al 2015, van Holstein et al 2021, 49 Cet (Pawellek et al 2019), HIP 73145 (HD 131835, Feldt et al 2017), HD 15115 (Engler et al 2019), HD 117214 (Engler et al 2020), and GSC 07396-00759 (Adam et al 2021), the latter four being detected at rather low signal to noise ratio in the available DPI observations. For 𝛽 Pictoris, the warped inner disk strongly biases the determination of the vertical scale height of the outer disk, rendering the modeling challenging.…”
Section: Observational Constraints On the Vertical Thicknessmentioning
confidence: 99%
“…For 𝛽 Pictoris, the warped inner disk strongly biases the determination of the vertical scale height of the outer disk, rendering the modeling challenging. The disk around 49 Cet is overall very extended and very faint (Pawellek et al 2019) and was therefore not considered in this study.…”
Section: Observational Constraints On the Vertical Thicknessmentioning
confidence: 99%
“…The disk was first imaged with Keck at 12.5 and 17.9 µm at sub-arcsecond resolution by Wahhaj et al (2007) who found a two-part disk best fit their observations: an inner disk composed of small grains that fit the MIR observations and an unresolved outer disk of larger grains. This continuum emission has since been observed in wavelengths ranging from from optical to submillimeter (Roberge et al 2013;Moór et al 2015;Hughes et al 2017;Choquet et al 2017;Pawellek et al 2019;Higuchi et al 2019).…”
Section: The 49 Ceti Debris Diskmentioning
confidence: 94%